2021
DOI: 10.1007/s00265-021-03003-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of boldness and exploratory behavior in giant mice from Gough Island

Abstract: Island populations are hallmarks of extreme phenotypic evolution. Radical changes in resource availability and predation risk accompanying island colonization drive changes in behavior, which Darwin likened to tameness in domesticated animals. Although many examples of animal boldness are found on islands, the heritability of observed behaviors, a requirement for evolution, remains largely unknown. To fill this gap, we profiled anxiety and exploration in island and mainland inbred strains of house mice raised … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Individuals who failed to adjust quickly would likely struggle in response to shifting resources, highlighting that shifts in resource availability can be a strong selection pressure for inherently bold, innovative, persistent, or flexible individuals. The understanding of the heritability of these behavioral traits is still developing, but research has identified genetic correlations with boldness in multiple vertebrate species ( Bubac et al, 2021 ; Stratton, Nolte & Payseur, 2021 ) and differential heritability among different behaviors in donkeys ( Equus asinus ; Navas González et al., 2019 ). Therefore, environmental changes that select for bold, innovative, or persistent individuals paired with the heritability of these traits could result in shifts in behavior at the population level over time.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who failed to adjust quickly would likely struggle in response to shifting resources, highlighting that shifts in resource availability can be a strong selection pressure for inherently bold, innovative, persistent, or flexible individuals. The understanding of the heritability of these behavioral traits is still developing, but research has identified genetic correlations with boldness in multiple vertebrate species ( Bubac et al, 2021 ; Stratton, Nolte & Payseur, 2021 ) and differential heritability among different behaviors in donkeys ( Equus asinus ; Navas González et al., 2019 ). Therefore, environmental changes that select for bold, innovative, or persistent individuals paired with the heritability of these traits could result in shifts in behavior at the population level over time.…”
Section: Discussionmentioning
confidence: 99%
“…To generate F2 mice, we conducted intercrosses between inbred strains of GI mice (produced in our laboratory) and mainland mice, the same strains used by Stratton et al . [ 20 ]. In 2009, GI mice were live-caught and shipped to the University of Wisconsin School of Veterinary Medicine Charmany Instructional Facility, where a breeding colony was established [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Husbandry and weighing protocols were identical to those applied by Stratton et al . [ 20 ] (see electronic supplementary material, file S1). F1s were generated by crossing mice from the GI strain and the mainland strain in both maternal directions ( figure 1 d ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations